TINJAUAN PRODUCTIVE MAINTENANCE MESIN LAMINASI PACKAGING PADA PT. ULTRA PRIMA PLAST - Fahrudin, Fahrudin; Sulistyo, Arif Budi (Prodi Teknik Industri, Fakultas Teknik, 2023)
This research was conducted to measure the effectiveness and application of the Total Productive Maintenance (TPM) method, especially on the Focused Improvement pillar on the Printing Packaging machine at PT. Ultra Prima Plast. The research was conducted using quantitative data and an Overall Equipment Effectiveness (OEE) analysis approach. The OEE value was analyzed using Six Big Losses (SBL) to find the dominant factor causing the loss. The loss factor is then classified with the 80/20% formula as a reference for making Fishbone Diagrams. Fishbone Diagram analysis is carried out to find the cause and effect or root causeof each loss. The root of the problem obtained is then given a suggestion for improvement and analyzed using the 5W+1H method. The results of the study obtained an average value of Overall Equipment Effectiveness (OEE) of 28%. Thisvalue is obtained from several calculations including the Availability Rate 97%, Performance Rate 20% and Quality Rate 98%. This value is still below the world category that has been seet by JIPM. which is 85%. The losses on the printing packaging machine are yield losses wich is 58% and reduce speed losses which is 23%. The roots on the problem found were the absence of planed maintenance and autonomus maintenance on Laminasi packaging machine and unmaintained environment inadequate knowlage of human resources and negligance of work procedures in the field.